The determinants of inbound tourism in China from different regions - Haichen Dou (2018)
© Published under licence by IOP Publishing Ltd. This study analyses the determinants of inbound tourism in China while considering the influence of regional distribution and income groups of 44 origin countries during the period from the year of 2006 to 2015. The empirical results show that inbound tourism in China is not a luxury good for a majority of tourists. At the same time, tourists from relatively developed regions pay more attention to tourism infrastructure construction and quality of tourism in China. Furthermore, compared to tourists from other regions, African tourists have a stronger desire to travel to China than other regions. In addition, increasing income of both high-income and lower middle-income countries has a positive effect on the demand for inbound tourism in China, which is on the contrary to the upper middle-income countries. Policies that improve the construction of tourism facilities, reduce entry barriers for African tourists, and provide citizens of the origin countries with an enabling environment for learning Chinese would attract more tourists from different regions to China.